Regionalism across the North-South divide : state strategies and globalization - Grugel, Jean (Routledge LondonGB, 1999)
Examines the trend towards regionalism in the contemporary world order. Provides some background to the changing position in the global order of the South and examines the competing theoretical perspectives on regionalism. Looks at politics within some semi-peripheral states and the role they play in building new regions. Discusses regional associations within three developing areas, where the region is taking on a middle position between the North and South.